Extraperitoneal Pelvic laparoscopic disconnection of accessory urethra from normal urethra in a case of urethral duplication - Nitin Pant; Satish Kumar Aggarwal (Wolters Kluwer Medknow Publications, 2014)
We report an extraperitoneal pelvic laparoscopic approach to disconnect accessory urethra from normal urethra in complete urethral duplication. First stage consisted of chordee correction, partial excision of the accessory urethra and glansplasty. In the second stage the remaining accessory urethra was disconnected from the normal urethra through a pre-peritoneal minimal access approach to the retropubic space. The remaining distal mucosa was ablated using monopolar cautery.